2016
DOI: 10.1002/app.43532
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical study of polymer‐polymer thin film interface under applied service conditions

Abstract: Single layer and multilayer polymer thin film coating on polymer substrate are gaining significant importance in different industries. The quantitative and qualitative estimation of interface response for thin film coating under different service conditions is significantly important from the perspective of modeling and designing novel materials. However, to characterize an interface between the soft polymer layer and soft polymer substrate is challenging because of the confinement effect, surface roughness, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…We restricted the maximum penetration depth to 10–12% of the TAT-BPy CONT fabric thickness while doing the indents to avoid the substrate effect. We completed the partial loading-full-unloading experiments with 33 cycles by progressively increasing the load (with an initial load of 10 μN and a peak load of 9000 μN) in each step and, after that, calculated the corresponding E r and H from each P – h curve (Figures b and S45). In general, the value of E r and H decreases progressively with the increase in load. However, an increase in the value of these parameters indicates the involvement of the substrate effect. , We identified a 100 μN load as the optimal load with minimal substrate effect on our sample. This was further validated by nanodynamic mechanical analysis (nano-DMA) studies (Figures c and S46, S47).…”
Section: Resultsmentioning
confidence: 99%
“…We restricted the maximum penetration depth to 10–12% of the TAT-BPy CONT fabric thickness while doing the indents to avoid the substrate effect. We completed the partial loading-full-unloading experiments with 33 cycles by progressively increasing the load (with an initial load of 10 μN and a peak load of 9000 μN) in each step and, after that, calculated the corresponding E r and H from each P – h curve (Figures b and S45). In general, the value of E r and H decreases progressively with the increase in load. However, an increase in the value of these parameters indicates the involvement of the substrate effect. , We identified a 100 μN load as the optimal load with minimal substrate effect on our sample. This was further validated by nanodynamic mechanical analysis (nano-DMA) studies (Figures c and S46, S47).…”
Section: Resultsmentioning
confidence: 99%
“…The hardness and reduced modulus values are given by the Oliver–Pharr equations below and are directly obtained from the instrument. H=PmaxAc Ac=f(hc)=C1hc2+C2hc+C3hc1/2+C4hc1/4+ Er=π2βsAc where, P max is the maximum load; C 1 , C 2 , C 3 , C 4 are constants and E r is the reduced Young's modulus; A c is the contact area; h c is the contact height; and s is stiffness of the material as expressed in above equations …”
Section: Resultsmentioning
confidence: 99%
“…where, P max is the maximum load; C 1 , C 2 , C 3 , C 4 are constants and E r is the reduced Young's modulus; A c is the contact area; h c is the contact height; and s is stiffness of the material as expressed in above equations. 46,47 High temperature treatment of blends resulted in significant improvement of E r and H values as shown in Figure 12. It is observed that E r value increases from 2.5 to 3.8 GPa for the pristine PVDF and H value increases from 80 to 240 MPa.…”
Section: Mechanical Properties Of Pvdf-p(vdf-trfe) Blendsmentioning
confidence: 95%
“…Nanoindentation and nanoscratch are depth-sensing experimental techniques which can be applied to estimate the adhesion strength of an interface. The strength of the polymer interface had been measured by some researchers using quasi-static indentation and nanoscratch tests. , In these studies, it is observed that the change in the slope of the load versus maximum load plot can successfully identify the interface during depth sensing. Different slopes are observed for interfaces of different strengths.…”
Section: Introductionmentioning
confidence: 99%